Stress Echocardiography and Major Cardiac Events in Patients with Normal Exercise Test - Calasans, Flávia Ricci (Sociedade Brasileira de Cardiologia, 2013)
BACKGROUND: Exercise test (ET) is the preferred initial noninvasive test for the diagnosis and risk stratification of coronary artery disease (CAD), however, its lower sensitivity may fail to identify patients at greater risk of adverse events. OBJECTIVE: To assess the value of stress echocardiography (SE) for predicting all-cause mortality and major cardiac events (MACE) in patients with intermediate pretest probability of CAD and a normal ET. METHODS: 397 patients with intermediate CAD pretest probability, estimated by the Morise score, and normal ET who underwent SE were studied. The patients were divided into two groups according to the absence (G1) or presence (G2) of myocardial ischemia on SE .End points evaluated were all-cause mortality and MACE, defined as cardiac death and nonfatal acute myocardial infarction (AMI). RESULTS: G1 group was comprised of 329 (82.8%) patients. The mean age of the patients was 57.37 ± 11 years and 44.1% were male. During a mean follow-up of 75.94 ± 17.24 months, 13 patients died, three of them due to cardiac causes, and 13 patients suffered nonfatal AMI. Myocardial ischemia remained an independent predictor of MACE (HR 2.49; [CI] 95% 1.74-3.58). The independent predictors for all-cause mortality were male gender (HR 9.83; [CI] 95% 2.15-44.97) and age over 60 years (HR 4.57; [CI] 95% 1.39-15.23). CONCLUSION: Positive SE for myocardial ischemia is a predictor of MACE in the studied sample, which helps to identify a subgroup of patients at higher risk of events despite having normal ET.